A concise lexicon of late biblical Hebrew: linguistic innovations in the writings of the Second Temple period - Hurvitz, Avi (Supplements to Vetus Testamentum, 2014)
"The Hebrew language may be divided into the biblical, Mishnaic, Medieval, and Modern periods. Biblical Hebrew has its own distinct linguistic profile, exhibiting a diversity of styles and linguistic traditions extending over some one thousand years as well as tangible diachronic developments that may serve as chronological milestones in tracing the linguistic history of Biblical Hebrew. Unlike standard dictionaries, whose scope and extent are dictated by the contents of the biblical concordance, this lexicon includes only 80 lexical entries, chosen specifically for a diachronic investigation of late biblical Hebrew. Selected primarily to illustrate the fifth-century 'watershed' separating classical from post-classical biblical Hebrew, emphasis is placed on 'linguistic contrasts' illuminated by a rich collection of examples contrasting classical biblical Hebrew with late biblical Hebrew, biblical Hebrew with Rabbinic Hebrew, and Hebrew with Aramaic"-- Provided by the publisher